Readiness Management in Handling COVID-19 Pandemic and Early Detection in The Referral Hospital in East Nusa Tenggara Province - Merlin, Ni Made; Vanchapo, Antonius Rino (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Covid-19 pandemic that is occurring now has rapidly and widely spread throughout the world. Various efforts are made to handle or suppress the number of cases, including readiness management in the emergency department until 7th May 2020. This study aimed to investigate readiness management in handling the Covid-19 pandemic in a referral hospital in Kupang, East Nusa Tenggara Province. This research represented a mix-method study. The samples were 20 emergency nurses at a Covid-19 referral hospital in Kupang. Data were collected using an interview that was distributed to respondents through Google forms. The questionnaire consisted of 12 questions about hospital readiness and 8 questions about early detection of Covid-19. Results showed that 90% of emergency nurses had performed early detection of Covid-19. The hospital readiness management in handling the Covid-19 pandemic was adequately good. Some obstacles were found during its implementation, such as the lack of personal protective equipment and health support tools, as well as patients’ dishonesty of traveling and contact history with COVID-19 patients.